Alchemy the dark art and curious science of creating magic in brands, business, and life - Sutherland, Rory ca. 20. Jh (Custom House, an imprint of William Morrow, 2021)
We think we are rational creatures. Economics and business rely on the assumption that we make logical decisions based on evidence. But we arent, and we dont. In many crucial areas of our lives, reason plays a vanishingly small part. Instead we are driven by unconscious desires, which is why placebos are so powerful. We are drawn to the beautiful, the extravagant and the absurd from lavish wedding invitations to tiny bottles of the latest fragrance. So if you want to influence peoples choices you have to bypass reason. The best ideas dont make rational sense: they make you feel more than they make you think. Rory Sutherland is the Ogilvy advertising legend whose TED Talks have been viewed nearly 7 million times. In his first book he blends cutting-edge behavioural science, jaw-dropping stories and a touch of branding magic, on his mission to turn us all into idea alchemists. The big problems we face every day, whether as an individual or in society, could very well be solved by letting go of logic and embracing the irrational
Originally published as Alchemy : the surprising power of ideas that don't make sense in the UK by WH Allen in 2019
Keywords: Verbraucherverhalten; Advertising / Psychological aspects; Marketing / Psychological aspects; Business